2020
DOI: 10.3390/ma13163589
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Photocatalytic Properties of Metal-Doped ZnO Nanofilms Grown on Graphene-Coated Flexible Substrates

Abstract: A series of metal element (Al, Fe, Mg and Ni)-doped ZnO (M-ZnO) photocatalysts have been successfully synthesized on graphene-coated polyethylene terephthalate (GPET) flexible substrate via the hydrothermal method. The effects of doped metals in ZnO were also studied on the crystal structure, morphology and photocatalytic performance. The photocatalytic experiment results indicated that, compared with Al-, Mg- and Fe-ZnO/GPET photocatalysts under ultraviolet (UV) light irradiation, Ni-ZnO/GPET had better photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…Sun et al reported a novel platform based on the reduced graphene/molybdenum disulfide films for plasmon-enhanced fluorescence, which has less optical loss and high sensitivities [ 181 ]. Yu et al improved the photocatalytic performance and degradation rate by using metal-doped ZnO nanofilms grown on graphene-coated flexible substrates [ 182 ]. Shao and his co-workers reviewed the two-dimensional (2D) plasmonic nanomaterials in the field of sensing.…”
Section: New Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sun et al reported a novel platform based on the reduced graphene/molybdenum disulfide films for plasmon-enhanced fluorescence, which has less optical loss and high sensitivities [ 181 ]. Yu et al improved the photocatalytic performance and degradation rate by using metal-doped ZnO nanofilms grown on graphene-coated flexible substrates [ 182 ]. Shao and his co-workers reviewed the two-dimensional (2D) plasmonic nanomaterials in the field of sensing.…”
Section: New Strategiesmentioning
confidence: 99%
“…graphene-coated flexible substrates [182]. Shao and his co-workers reviewed the two-dimensional (2D) plasmonic nanomaterials in the field of sensing.…”
Section: New Strategiesmentioning
confidence: 99%